Portuguese cinema (1960-2010) : consumption, circulation and commerce - Graça, André Rui (Woodbridge, Suffolk, UK : Tamesis, 2021)
Why has Portugal's vibrant and creative cinema industry not been more commercially successful?
Introduction Chapter I -- The 'Unsuccess' of a National Cinema Chapter II -- Spectators and Contrasts in Culture Chapter III -- Visibility, Artistic Prestige, and Circulation Chapter IV -- Portuguese Cinema Laws (1971-2006) General Conclusions Bibliography Appendix 1 Appendix 2
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Motion picture industry -- Portugal -- History; Motion pictures -- Portugal -- History; Cinéma -- Industrie -- Portugal -- Histoire; Cinéma -- Portugal -- Histoire; Motion picture industry; Motion pictures; Portugal; History